Proton MagneƟc Resonance Spectroscopy in Asperger’s Syndrome: CorrelaƟons with Neuropsychological Test Scores - ÖNER, Özgür (Turk Psikiyatri Derg, 2009)
OBJECTIVES: It has been shown that autistic spectrum patients have impaired theory of mind (ToM) performance; however, no study has investigated the relationship between ToM performance and brain neurochemistry in these patients. The present study aimed to investigate the correlations between dorsolateral prefrontal cortex (DLPFC) and anterior cingulate cortex (ACC) N-acetyl-aspartate (NAA)/choline (Cho), NAA/creatine (Cr), and Cho/Cr values based on (1)H magnetic resonance spectroscopy and ToM tests. METHOD: The study sample included 13 adult, right-handed, Caucasian males with Asperger’s syndrome (AS) (age range: 17–37 years) and 20 controls matched by age, gender, handedness, and Wechsler Adult Intelligence Scale, Revised (WAIS-R) full-scale IQ scores. RESULTS: AS cases had significantly lower ToM performance. DLPFC NAA/Cho levels were inversely correlated to ToM scores (r = −0.738, P = 0.004). On the other hand, ToM performance improved as DLPFC Cho/Cr increased (r = 0.656, P = 0.015). ACC MRS variables were not significantly correlated with ToM performance in the AS group. No significant correlation was observed between ACC or DLPFC MRS variables and ToM performance in the control group. Discussion: Because NAA/Cho was inversely correlated with ToM performance and Cho/Cr was correlated with ToM performance, it can be suggested that the Cho level was related to better ToM test performance in the AS group. An increase in the Cho peak was associated with an increase in membrane breakdown or turnover. The Cho peak was also thought to reflect cellular density and astrocytosis. It is suggested that membrane turnover and astrocytosis might affect cognitive functioning.